The new helping the old: Social media as a facilitator for variety seeking in food choices of the grey population - Teerakapibal, Surat; Melanthiou, Yioula (My University, 2020)
Purpose: Evidence has shown that the population is growing “increasingly gray” and growing too are the concerns for the elderly population with regards to their food choices. Being well informed and seeking variety in food choices increase the likelihood that people will be better nourished and hence improve the quality of life for this group, and at the same time be beneficial for society overall. The purpose of this paper is to determine the influence of social network usage on food choice. Design/methodology/approach: This paper uses a series of logistic and ordinal logistic regression models using Health and Wellness Survey data and Internet Usage Survey data from the National Statistical Office of Thailand. The data sets contain information on health status, food consumption, proportion of population using the internet, and detailed demographics. Findings: Empirical results show the association between variety in food consumption and lower probability of being chronically ill. More importantly, social network usage is found to significantly encourage variety seeking behavior (VSB) in food consumption. Research limitations/implications: Though the benefit of using Thai data sets lies in the fact that there is a large variation in network usage across the country, this study should extend beyond Thailand to establish greater external validity. Practical implications: Marketing new food products must not neglect the promotion through social networks due to its potential to encourage VSB in food consumption. Moreover, while sometimes this particular age group may be somewhat marginalized and not targeted to enough, this research study has shown that it is indeed an important segment. Social implications: In order to relieve the growing financial burdens in health care for citizens, policy makers should encourage this ageing population to eat a balanced diet. Social media is shown to be an effective medium for promoting variety in food consumption. Notably relevance, engagement and emotion are principal elements for social network platforms targeting aging consumers. Originality/value: This paper utilizes two large representative data sets with detailed information which does not only allow for controlled analyses but also provides implications for the growing aging consumer segment.
Keywords: Social networks; Elderly; Social media; Ageing